Vegetation structure and soil organic carbon storage across northern forest-tundra ecotones in continuous permafrost - H. Travers-Smith; N.C. Coops; T.C. Lantz; M. Hamp; D. Ignace; M.A. Wulder; J. van der Sluijs (Arctic Science)
Climate change is altering northern vegetation structure and below-ground carbon storage. Expanding forest and shrub cover has decreased soil organic carbon (SOC) storage in some parts of the forest-tundra ecotone. In this study, we linked measurements of SOC with terrain and vegetation structure derived from drone imagery across treelines underlain by continuous permafrost in the Northwest Territories, Canada. We classified sites into three treeline types representing differences in vegetation productivity and topography. Between treeline types, we observed differences in C:N ratios and organic matter depth related to the rate of soil carbon turnover and SOC storage. Overall, SOC showed small positive relationships with tree stem density and average canopy height. We did not find evidence that expanding tree- and shrublines would result in losses of SOC storage in our study area. Instead, topography and landscape drainage patterns, rather than vegetation structure may be more important predictors of SOC storage. We used medium resolution satellite data to extend predictions of treeline type across our study area. The majority of predicted treelines (82%) showed positive relationships between vegetation height and SOC storage. Our findings highlight the value of integrating vegetation structure and landscape features in understanding carbon dynamics in the forest-tundra ecotone.